The role of investor relations and good corporate governance on firm performance in the case of the companies listed on the Bucharest Stock Exchange - Bogdan Aurelian Mihail; Dalina Dumitrescu; Daniela Serban; Carmen Daniela Micu; Adriana Lobda (Journal of Risk and Financial Management, 2021)
The objective of this paper is to investigate the role of Investor Relations (IR) in the performance of companies listed on the Bucharest Stock Exchange. The study is motivated by the findings in the literature that investor relations may boost information disclosure, analyst following, institutional investor share, liquidity, and business valuation. The current article contributes to the relevant literature by making use of the recently released unique database of VEKTOR scores on company investor relations for 2019 and 2020. The main finding based on regression methodology shows that IR scores have a strong positive relationship with firm performance. Specifically, a one standard deviation rise in the IR score corresponds to a 2.6% rise in company ROA. Companies may be advised to strengthen their investor relations based on these findings about the beneficial role of investor relations.
Keywords: 330; corporate governance; investor relations; firm performance; Bucharest Stock Exchange; Romania